Análisis de las figuras retoricas en los spots publicitarios de coca cola - Andagana Lumbi, Margoth Jacqueline (2019)
Advertising is a tool used to carry information or a message to the client or user, it has various forms of expression or interpretation depending on the brand, slogan, proposal, product or promotion, large food chains, have been used in most the advertising spots cases based on an abstract construction, in which elements have been used that allow the consumer to play with their imagination and interpretation of the facts, but always focusing on their capture and that it enters the person's psyche; In the present case of research or study, the advertising spots made by one of the world's largest soft drink chain, the Coca-Cola Company, will be taken into account, which has evolved and transformed with strategies to persuade people taking into account the political, social problems knowing how to create character and the product taking in the background only as an identification of happiness. In most spots, you can see how he has evolved depending on the time and taking the family into account. In addition to theoretical research, criteria obtained through interviews conducted by retailers and consumers of this beverage will be analyzed, which, despite being considered harmful to health, does not decrease its sales level, but has used advertising strategies, with which ensures that it has no sugar and that it has reinvented its formula guaranteeing its same flavor